Extrapyramidal syndrome - Panda, Akhila Kumar (BMJ Publishing Group, 2014)
Organophosphate (OP) poisoning is a common occurrence in the rural areas of developing countries like India. Acute cholinergic crisis is one of the important causes of mortality related to OP poisoning. Delayed peripheral neuropathy, extrapyramidal syndromes and neuropsychiatric manifestations are the major consequences of secondary neuronal damage. This case illustrates a 14-year-old girl who ingested 50 mL of OP pesticide and developed extrapyramidal symptoms in the form of parkinsonism and hand dystonia in spite of immediate medical attention. MRI of the brain with T2, fluid attenuated inversion recovery and diffusion-weighted sequences revealed bilateral symmetrical basal ganglia hyperintensities. Further follow-up revealed a significant clinical improvement with marked resolutions of the brain lesions. The reversible extrapyramidal symptoms with disappearance of neuroimaging findings without neuropathy or neuropsychiatric manifestations are unusual in OP poisoning.